PO 48 - Eye-Surgery in a patient with Alport Syndrome – about a clinical case Introduction - Parra, André; Almeida, Carolina; Paulos, Jorge; Lima, Filomena (Revista da Sociedade Portuguesa de Anestesiologia, 2023)
x